Realizing the Ideal Model of Digital Islamic Boarding Schools: a Systematic Literature Review Analysis - Ahmad Fauzi; Muhamad Arif; Ali Mustofa (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2025)
To analyze the transformation of Islamic boarding schools (Pesantren) in the digital era, assess the contribution of digital technology to Islamic boarding schools, and propose the ideal model for digital Islamic boarding schools. The study uses a systematic literature review method utilizing the